Design and development of miniaturized antenna for wireless energy harvesting - Saranathan, Gayathri (Nanyang Technological University, 2022)
The objective of this thesis is to design and simulate miniaturized antennas for wireless energy harvesting applications. A miniaturized single-band dual-polarized (SBDP), and dual-band dual-polarised (DBDP) stacked patch antenna using coaxial-probe feed is designed, and simulated for RF energy harvesting applications. The ambiance has an abundance of RF Energy radiated by numerous sources like Base Stations, WiFi routers, Satellite systems, and various other wirelessly transmitting systems. The sources such as solar, thermal, mechanical, and wind are used for harnessing wireless energy from the surrounding, these methods have some disadvantages such as: (i) These energies are present in constrained environment, such as the need for sunlight for generating solar energy, need for a large area with windmills in windy regions, scorching temperatures for thermal energy which are not commonly available in the environment for use, (ii) These energies cannot be harnessed round the clock, for instance - the solar energy can only be harvested when there is presence of sunlight, (iii) The harnessing system is not miniaturized to support the low-profile sensor/actuator system, instead it occupies large area and is best suited for large-scale energy harnessing. For an automated sensor/actuator system, which requires constant supply of energy without constraints and saturation, where low received power is tolerable, the abundant RF signals present in the ambiance can be exploited to harvest small-scale renewable energy round the clock, as the RF energy is used for various applications and can be accessed easily through a miniaturized antenna. Although the power generated through RF energy is low, it is sufficient to power up sensor and actuator system, and can be an alternative for low-power battery-backed systems. The RF energy in the ambiance exists in any polarisation and orientation, therefore a dual polarized antenna is preferred which can receive vertical/horizontal polarized RF waves. In this thesis, SBDP miniaturized stacked patch antenna is designed using Rogers RO4003C substrate with a er equal to 3.55 is designed at 2.4 GHz with a dimension of 30mm x 30mm, and a symmetric square patch radiator is designed with dimensions 15.9mm x 15.9mm obtained after iterating around the actual dimension value obtained from the equations. The two ports are fed to the patch at 5.77mm from the center. A bandwidth of 88 MHz at the two ports is obtained at 50 Ohm Simulated Reference Impedance. A dual-band antenna is designed, which includes a 2.4GHz symmetric square patch of dimension 15.9mm x 15.9mm with 3mm symmetric triangular slits for better resonating performance during stacking and structural innovation, and a 5.8GHz circular patch with a radius of 7.92mm. Bandwidth of about 78.6 MHz at 2.4 GHz and 380 MHz at 5.8GHz frequency is obtained. An outer to inner diameter ratio of 4.629 mm for the coaxial feeding is maintained to achieve a characteristic impedance of 50 Ohms. The probe feeding technique is used for the two main antenna designs, which will be directly connected to the rectifiers. Since the efficiencies of the two main antennas designed are over 75% at both the ports, the antenna can be implemented anywhere and is a compact design for harvesting the RF energy which could be yielded for low DC power requiring applications.